1992
DOI: 10.1007/bf00298500
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of sodium fluoride into cortical bone does not impair the mechanical properties of the appendicular skeleton in rats

Abstract: Clinical studies on the use of sodium fluoride (NaF) in osteoporotic patients have demonstrated increased spinal bone mass without a reduction in vertebral fracture incidence, and a trend towards reduced appendicular bone mass with an increase in peripheral fracture incidence. As previous reports have suggested that NaF becomes incorporated into bone's crystal structure, possibly affecting bone strength, we sought to examine the relationship among bone fluoride content, bone mass, and skeletal fragility. Twent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 14 publications
0
12
1
Order By: Relevance
“…These indicate a beneficial effect of xylitol on the mechanical properties of both the cortical and trabecular part of the bone, and negate the possibility that dietary xylitol, in spite of the increased bone mineral content, could cause such qualitative changes in bone that might compromise the mechanical properties of bone. In this respect the present results with xylitol differ from the results of recent rat model studies with fluoride [12,30] where the increased bone mass and geometric properties did not unambiquously lead to increased bone strength.…”
Section: Discussioncontrasting
confidence: 85%
“…These indicate a beneficial effect of xylitol on the mechanical properties of both the cortical and trabecular part of the bone, and negate the possibility that dietary xylitol, in spite of the increased bone mineral content, could cause such qualitative changes in bone that might compromise the mechanical properties of bone. In this respect the present results with xylitol differ from the results of recent rat model studies with fluoride [12,30] where the increased bone mass and geometric properties did not unambiquously lead to increased bone strength.…”
Section: Discussioncontrasting
confidence: 85%
“…Anabolic effects of fluoride in the rat skeleton have not been demonstrated consistently [13,16]. Furthermore, rat long bones do not undergo osteonal remodeling which is the major Correspondence to: C. H. Turner Calcif Tissue Int (1997) 61:77-83 …”
Section: Animalsmentioning
confidence: 96%
“…When the fluoride content in the bone mineral of rats reached 10,000 parts per million (ppm), bone strength was decreased by about 13% with normal calcium intake (Turner et al, 1992) or by as much as 45% when fluoride intake was associated with calcium deficiency (Beary, 1969;Riggins et al, 1974). Other studies showed no effect of fluoride on bone strength, even at high doses (Naylor and Wilson, 1967;Einhorn et al, 1992). To date, animal studies of fluoride effects on bone have used young and healthy experimental animals exclusively.…”
Section: Introductionmentioning
confidence: 95%